2016
DOI: 10.1055/s-0036-1593731
|View full text |Cite
|
Sign up to set email alerts
|

Titanium versus Stainless-Steel Plating in the Surgical Treatment of Distal Radius Fractures: A Randomized Trial

Abstract: Our purpose was to compare postoperative complications and rate of plate removal in titanium and stainless-steel plating of distal radius fractures (DRF). Patients following DRF were randomly fixed with titanium or stainless-steel plates using the same plating system. Complications, second surgeries, and plate prominence were documented. A total of 41 patients were treated with stainless-steel and 22 with titanium plates. Average follow-up was 60???5.6 months. There was no difference in demographics, fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In the present study the mean duration of plating in Group S was 24.40 ± 1.95 weeks and mean duration of plating in Group T was 22.60 ± 2.94 weeks with no statistical significant difference (P>0.05) Shakir S et al 6 also observed no difference in removal rates between the groups which was in accordance with our study. "The comparison of mean duration of follow up among both groups showed that mean duration of follow up in Group S was 6.23 ± 1.22 months and mean duration of follow up in Group T was 5.93 ± 1.28months with no statistical significant difference (P>0.05), similar was concluded by Shakir S et al 6 In present study the mean duration of bone union in Group S was 23.26 ± 1.43 weeks and mean duration of bone union in Group T was 21.60 ± 2.47 weeks with statistical significant difference (P<0.05). The mean operative time in Group S was 72.26 ± 6.39 minutes and in Group T was 68.46 ± 4.31minutes with no statistical significant difference (P>0.05).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the present study the mean duration of plating in Group S was 24.40 ± 1.95 weeks and mean duration of plating in Group T was 22.60 ± 2.94 weeks with no statistical significant difference (P>0.05) Shakir S et al 6 also observed no difference in removal rates between the groups which was in accordance with our study. "The comparison of mean duration of follow up among both groups showed that mean duration of follow up in Group S was 6.23 ± 1.22 months and mean duration of follow up in Group T was 5.93 ± 1.28months with no statistical significant difference (P>0.05), similar was concluded by Shakir S et al 6 In present study the mean duration of bone union in Group S was 23.26 ± 1.43 weeks and mean duration of bone union in Group T was 21.60 ± 2.47 weeks with statistical significant difference (P<0.05). The mean operative time in Group S was 72.26 ± 6.39 minutes and in Group T was 68.46 ± 4.31minutes with no statistical significant difference (P>0.05).…”
Section: Discussionsupporting
confidence: 83%
“…(P>0.05) Overall 80% subjects were males and 20% were female, with no statistical significant difference seen among both groups with respect to gender (P>0.05)It was observed that majority of patients had road traffic accident (73.33%) followed by trauma (20%) There was no statistical significant difference seen among both groups with respect to mechanism of injury (P>0.05). Shakir S et al 6 studied Titanium versus Stainless-Steel plating in the surgical treatment of distal radius fractures observed no difference in demographics, fracture characteristic between the groups. Holzach P et al 7 studied comparison of steel and titanium dynamic compression plates used for internal fixation tibia observed no demographic difference between two groups, which was similar with our study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A significant difference was not detected in rate of plate removal based on metal, nor was there a difference in the soft-tissue complication rates between the 2 groups. [14] Rozental et al [13] also did not detect a significant difference based on plate composition in complication or plate removal in a retrospective review of distal radius fractures.…”
Section: Radiusmentioning
confidence: 93%
“…[12] Despite the variation seen in biomechanical studies, the clinical studies had no evidence of mechanical failure or nonunion/malunion. [13][14][15] Plate failure or breakage in distal radial fracture fixation is exceedingly rare, with no instances of this complication in the multiple series reviewed.…”
Section: Radiusmentioning
confidence: 99%